"Re-Emergence" of Silicosis and Coal Workers Pneumoconiosis in Australia. (1st November 2020) - Penrose, Beris
Abstract : Some reporters, politicians, and doctors have described current cases as a "re-emergence" of these diseases, based on the notion that they had been eliminated. However, silicosis persisted in centuries-old industries like sandblasting and stonemasonry and coal workers pneumoconiosis (CWP) continued in coal mining. Until recently, their presence was obscured by a combination of factors such as misdiagnosis, especially if there was a history of smoking; the failure to follow up workers thought to have silicosis or CWP; the long latency period between dust exposure and disease onset that can conceal the link between the two; and the lack of data collection that may have revealed their presence. As the recent Queensland government inquiry into CWP noted, current cases are more accurately a reidentification.